Metabolism of Dietary and Microbial Vitamin B Family in the Regulation of Host Immunity - Yoshii, Ken; Hosomi, Koji; Sawane, Kento; Kunisawa, Jun (Frontiers in Nutrition, 2019)
Vitamins are micronutrients that have physiological effects on various biological responses, including host immunity. Therefore, vitamin deficiency leads to increased risk of developing infectious, allergic, and inflammatory diseases. Since B vitamins are synthesized by plants, yeasts, and bacteria, but not by mammals, mammals must acquire B vitamins from dietary or microbial sources, such as the intestinal microbiota. Similarly, some intestinal bacteria are unable to synthesize B vitamins and must acquire them from the host diet or from other intestinal bacteria for their growth and survival. This suggests that the composition and function of the intestinal microbiota may affect host B vitamin usage and, by extension, host immunity. Here, we review the immunological functions of B vitamins and their metabolism by intestinal bacteria with respect to the control of host immunity.